Social context od pain perception: the role of other people's presence and physical distance. - Modić Stanke, Koraljka; Ivanec, Dragutin (2010)
The aim of this study was to investigate the importance of passive person’s presence for the experience of pain induced by thermal stimuli in experimental conditions. Several previous studies suggested that mere presence of others can induce beneficial outcomes in people experiencing experimentally induced pain. Participants were involved in two different experimental situations – one in which they were completely alone in the room while experiencing pain and another in which they were, while experiencing pain, accompanied by an unfamiliar individual (passive observer), presented as unimportant for this experiment. There was no social interaction between participant and the passive observer during painful simulation. To explore more closely the possible nature of this effect of social context, the distance between passive observer and the participant was varied in this experiment. When participants were, during painful stimulation, accompanied by an unfamiliar individual, passive observer was in one group relatively close to the participant (50 cm), and in other group somewhat further away (150 cm). Measures of pain experience used in this study were pain threshold, pain tolerance, and also subjective assessment of intensity and general unpleasantness of pain experienced in this study. Results indicated no effect of other people’s presence on pain experience. There was no difference, in any measure of pain experience, between situation in which people experienced pain alone and the one in which they were accompanied by an unfamiliar individual. No effect of distance and also no interaction of distance and presence of passive observer were found in this study.
Projekt MZOS
Projekt MZOS
ENG